erbB2 Overexpression in Uterine Serous Cancer: A Molecular Target for Trastuzumab Therapy - Karim S. ElSahwi; Alessandro D. Santin (Hindawi Limited, 2011)
Endometrial cancer is the most common female genital tract malignancy in the United States. Type I endometrial cancer is usually diagnosed at an early stage, and has a good prognosis. Type II is very aggressive, and is responsible for most uterine cancer relapses and deaths. Uterine serous adenocarcinomas (USC) constitute the majority of Type II variants. They have a higher propensity for lymph node and distant metastases. They are frequently aneuploid and associated with p53 mutations. erbB2 overexpression in USC has been described. The incidence, which is higher in African Americans, ranges from 18-80%. erbB2 overexpression was found to be associated with higher stage, chemoresistance, and worse survival. Trastuzumab a humanized mAb was approved by the FDA for treatment of breast cancers that overexpress erbB2 in combination with standard chemotherapy. Evidence of trastuzumab activity in USC has been reported in vitro, as well as in case reports of advanced and recurrent cases. Promising results were obtained in these heavily pretreated patients either with trastuzumab alone or in combination with chemotherapy. This supports the hypothesis that trastuzumab may very well be an attractive and viable treatment option for advanced stage USC tumors that overexpress the erbB2, and is worthy of further study.